A Neo-Aramaic Version of a Kurdish Folktale. (2nd September 2020) - Häberl, Charles; Kuzin, Nikita; Loesov, Sergey; Lyavdansky, Alexey
Abstract: Versions of the folktale Zêrka Zêra (in Kurdish)/Stērka Zerá (in Ṭuroyo) circulate throughout southeastern Anatolia. The story belongs to a widely-disseminated tale type, the 'Bear's Wife', which concerns a young woman who is abducted by a bear (or other wilderness creature) and is forced to spawn and rear his children before escaping or being rescued. The following Ṭuroyo version was recorded during the 2018 winter field season of the Russian expedition to Ṭur Abdin in the village of Ḥaḥ/Anıtlı from a speaker of the dialect of Bequsyone. It represents the first scholarly publication not only of the Ṭuroyo version, but of any version of this folktale. In addition to the folktale and a translation, the study includes a glossary of the vocabulary used within the text, reflecting some Ṭuroyo words that have not been documented elsewhere. The paper also discusses the motifs of the Stērka Zerá folktale according to the standard classification scheme of folk motifs.